Effects of Butylated Hydroxytoluene and Butylated Hydroxyanisole on Viscosity and Breakdown Voltage of Palm Oil - Yenni Afrida; Herman H Sinaga; Dewi A. Iryani; Nining Purwasih; Diah Permata (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2026)
In the electric power system, insulating oil plays a pivotal role in separating two or more electrical conductors with different voltages. This separation is crucial to prevent unintended electrical connections or sparks that could compromise the system's safety and integrity. Mineral-based insulating oil is disadvantageous because it is classified as a mineral oil. This classification indicates that the waste is non-biodegradable, meaning biological processes cannot break it down. This characteristic can hurt the environment. Therefore, alternative efforts must be made to use liquid insulation, such as environmentally friendly vegetable oils. Vegetable oils are unsuitable as insulating oils due to their high viscosity, low oxidation stability, and good lubricity. A proposed solution to reduce palm oil viscosity involves adding additives. The dilution process can be enhanced by incorporating various additives, including butylated hydroxytoluene and butylated hydroxyanisole. The present study utilizes the Megger OTS80Af to assess the breakdown voltage and viscosity of the subject material. Vegetable oils are unsuitable as insulating oils due to their high viscosity, low oxidation stability, and good lubricity. A proposed solution to reduce palm oil viscosity involves adding additives. The dilution process can be enhanced by incorporating various additives, including butylated hydroxytoluene and butylated hydroxyanisole. The present study utilizes the Megger OTS80Af to assess the breakdown voltage and viscosity of the subject material. The experimental findings indicate that crude palm oil, when augmented with butylated hydroxytoluene and butylated hydroxyanisole, is deemed unsuitable for utilization as a transformer insulation medium. This determination is predicated on its inability to comply with the stipulated criteria outlined in SPLN 49-91: 1982, specifically the minimum breakdown voltage of 30 kV/2.5 mm for transformer insulation oil.